PENETAPAN UPAH MINIMUM PROVINSI (SUATU KAJIAN HUKUM PROGRESIF) - Mulyadi, Mulyadi (Katalogis, 2016)
The problems are formulated as: 1) Has the minumum subsistance wage and the implementation of wage system protected the workers/laborer?, 2) Has the minimum subsistance wage contributed to the workers/laborers’ welfare? It is under the supervision of Yasin Nahar and Surahman. This is normative research using qualitative analysis method. The research aimed at finding out that the minumum subsistance wage and the waging system stipulated by the local goverment have provided protection for workers/laborers in terms of their welfare. Progressive law reviews the legal procedure within different period. Legal procedure refers to the integration of various factors as the elements such as mission of law, paradigm used, the knowledge on constitutional regulation law, the use of specific theories. It also includes attitudes and psychological matters such as intention, commitment, dare, determination, emphaty, as well as compassion. The provincial minumum subsistance wage in Tolitoli Regency has not been fully provided welfare for the workers/laborers and employees due to the fact that some employers interpreted the meaning of minimum subsistance wage that if the workers/laborers have been payed with the minimum subsistance, the employers feel that they already satisfy their obligation based on the statements on the regulations.